Brand strategies in social media in hospitality and tourism - Moro, Sérgio (2018)
Moro, S., & Rita, P. (2018). Brand strategies in social media in hospitality and tourism. International Journal of Contemporary Hospitality Management, 30(1), 343-364. DOI: 10.1108/IJCHM-07-2016-0340 --- %ABS3%